2021
DOI: 10.12968/hmed.2020.0584
|View full text |Cite
|
Sign up to set email alerts
|

The interplay between atrial fibrillation and acute myocardial infarction

Abstract: Atrial fibrillation is the most frequently occurring supraventricular arrhythmia in patients presenting with acute myocardial infarction. It is associated with worse outcomes when it coexists with acute myocardial infarction and results in increased morbidity and mortality. Both conditions are closely related to each other and share similar pathophysiological pathways. The management of atrial fibrillation in patients with acute myocardial infarction is challenging since triple antithrombotic therapy is indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Studies have shown that when AF occurs, there is a sustained prothrombotic and inflammatory environment through the activation of platelets, the generation of thrombin, and the induction of endothelial dysfunction, which can exponentially increase the risk for myocardial infarction [ 2 ]. This, in conjunction with intermittent episodes of tachycardia, such as seen in this patient, can induce a demand-supply mismatch and further induce myocardial infarction [ 8 ]. This creates a bidirectional relationship between myocardial infarction and AF, which can be attributed to the similar risk factors and disease pathogenesis between the two conditions [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that when AF occurs, there is a sustained prothrombotic and inflammatory environment through the activation of platelets, the generation of thrombin, and the induction of endothelial dysfunction, which can exponentially increase the risk for myocardial infarction [ 2 ]. This, in conjunction with intermittent episodes of tachycardia, such as seen in this patient, can induce a demand-supply mismatch and further induce myocardial infarction [ 8 ]. This creates a bidirectional relationship between myocardial infarction and AF, which can be attributed to the similar risk factors and disease pathogenesis between the two conditions [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, these patients are less likely to be treated with appropriate antithrombotic agents. To help reduce the risk for myocardial infarctions, being able to identify the wide variety of symptoms of AF in addition to screening for AF can help physicians recognize AF early on in the disease course and initiate preventative treatment [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…The SWOT analysis method is an analysis method that measures the internal competitive environment and competitive conditions of the organization, analyzes the advantages and disadvantages and identifies the challenges faced by the related work, and further formulates and implements the solution according to the specific analysis results, so that the related work can be effectively solved. [ 12 ]. The study believed that introducing it into nursing management could objectively and comprehensively analyze the internal and external environment of nursing organization, formulate scientific nursing countermeasures according to the constructed situation matrix, and enhance the scientificity of nursing management and the market adaptability of nursing organization [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Atrial fibrillation shares a couple of risk factors with AMI, such as aging, hypertension, obesity, diabetes, alcohol consumption, and sleep-disordered breathing ( 4 , 5 , 18 ). Therefore, the two diseases may share similar pathophysiological pathways, and the co-occurrence of these two diseases seems not to be avoidable ( 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…The antithrombotic therapy for AMI-NOAF patients is contradictory. For AMI, dual antiplatelet therapy (DAPT) with aspirin and a P2Y 12 inhibitor is indicated to prevent stent thrombosis, ( 17 ) while in AF patients, oral anticoagulant (OAC) therapies including vitamin K antagonists (VKAs) or non-vitamin K oral anticoagulants (NOACs) are more effective in preventing stroke and other thromboembolic events ( 18 , 19 ). However, triple therapy combining DAPT with an anticoagulant is usually associated with an increased rate of excessive bleeding, which limits the clinical application ( 20 ).…”
Section: Introductionmentioning
confidence: 99%